PTK7/Otk interacts with Wnts and inhibits canonical Wnt signalling. - Peradziryi, H.; Kaplan, N.A.; Podleschny, M.; Liu, X.; Wehner, P.; Borchers, A.; Tolwinski, N.S. (The EMBO Journal, 2011)
Wnt signalling is an evolutionarily conserved pathway that directs cell-fate determination and morphogenesis during metazoan development. Wnt ligands are secreted glycoproteins that act at a distance causing a wide range of cellular responses from stem cell maintenance to cell death and cell proliferation. How Wnt ligands cause such disparate responses is not known, but one possibility is that different outcomes are due to different receptors. Here, we examine PTK7/Otk, a transmembrane receptor that controls a variety of developmental and physiological processes including the regulation of cell polarity, cell migration and invasion. PTK7/Otk co-precipitates canonical Wnt3a and Wnt8, indicating a role in Wnt signalling, but PTK7 inhibits rather than activates canonical Wnt activity in Xenopus, Drosophila and luciferase reporter assays. Loss of PTK7 function activates canonical Wnt signalling and epistasis experiments place PTK7 at the level of the Frizzled receptor. In Drosophila, Otk interacts with Wnt4 and opposes canonical Wnt signalling in embryonic patterning. We propose a model where PTK7/Otk functions in non-canonical Wnt signalling by turning off the canonical signalling branch.